Reconstructing the Paradigm of Knowledge Integration in Islamic Education: A Critical Examination of Adian Husaini’s Epistemological Thought - Kailani; Devi; Ismegawati; Benny prasetiya (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
This article aims to reconstruct the paradigm of knowledge integration in Islamic education through a critical examination of Adian Husaini’s epistemological thought. The study is motivated by the persistent challenges of the secularization of knowledge, educational dichotomy, disciplinary fragmentation, and the moral and spiritual crises that continue to characterize contemporary Islamic education. Within this context, Adian Husaini’s thought is particularly relevant because it offers a critique of the secular paradigm of knowledge and positions the Islamic worldview as the foundation for reconstructing the epistemology of Islamic education. This research employs a qualitative approach using a library research design. Data were collected from Adian Husaini’s works, literature on the philosophy of Islamic education, reputable journal articles, and recent studies on knowledge integration and the Islamization of knowledge. Data analysis was conducted through a critical-hermeneutic approach and epistemological discourse analysis. The findings reveal that Adian Husaini not only rejects the dichotomy between religious and secular sciences but also proposes a tawhid-based paradigm of knowledge integration that positions revelation as the ontological, epistemological, and axiological foundation of knowledge. Knowledge integration is understood not merely as the incorporation of religious elements into the curriculum or as a form of religious symbolism, but rather as a reconstruction of a scientific worldview that integrates revelation, reason, empirical experience, intuition, adab, and the civilizational goals of Islam. The novelty of this study lies in its effort to reconstruct knowledge integration as an epistemological project rooted in the Islamic worldview, adab, and the paradigm of tawhid within Adian Husaini’s intellectual framework, rather than viewing it solely as curricular or institutional integration. This article argues that the paradigm of knowledge integration developed by Adian Husaini holds significant relevance for the advancement of contemporary Islamic education, particularly in addressing the challenges of secularization, digital transformation, knowledge relativism, and the global moral crisis